Thymocyte migration: an affair of multiple cellular interactions? - Savino W.; Ayres Martins S.; Neves-dos-Santos S.; Smaniotto S.; Ocampo J.S.P.; Mendes-da-Cruz D.A.; Terra-Granado E.; Kusmenok O.; Villa-Verde D.M.S. (Brazilian Journal of Medical and Biological Research, 2003)
Cell migration is a crucial event in the general process of thymocyte differentiation. The cellular interactions involved in the control of this migration are beginning to be defined. At least chemokines and extracellular matrix proteins appear to be part of the game. Cells of the thymic microenvironment produce these two groups of molecules, whereas developing thymocytes express the corresponding receptors. Moreover, although chemokines and extracellular matrix can drive thymocyte migration per se, a combined role for these molecules appears to contribute to the resulting migration patterns of thymocytes in their various stages of differentiation. The dynamics of chemokine and extracellular matrix production and degradation is not yet well understood. However, matrix metalloproteinases are likely to play a role in the breakdown of intrathymic extracellular matrix contents. Thus, the physiological migration of thymocytes should be envisioned as a resulting vector of multiple, simultaneous and/or sequential stimuli involving chemokines, adhesive and de-adhesive extracellular matrix proteins, as well as matrix metalloproteinases. Accordingly, it is conceivable that any pathological change in any of these loops may result in the alteration of normal thymocyte migration. This seems to be the case in murine infection by the protozoan parasite Trypanosoma cruzi, the causative agent of Chagas' disease. A better knowledge of the physiological mechanisms governing thymocyte migration will provide new clues for designing therapeutic strategies targeting developing T cells.